Design and Fabrication the Nearshore Wave Energy Converter - Phan Công Bình; Nguyễn Nhựt Phi Long; Đỗ Tiến Sĩ (Journal of Technical Education Science, 2025)
This paper presents the computational analysis, design and experimental fabrication of a nearshore wave energy conversion and absorption device (Wave Energy Converter – WEC) developed to harness and convert the mechanical energy of ocean waves into electrical power. The device is specifically designed to operate efficiently under nearshore wave conditions and may also contribute to reducing wave energy impacting coastal dikes, thereby supporting erosion mitigation efforts. Initially, the working principle and structural configuration of the WEC are thoroughly described. Based on the drive system schematic and the geometric parameters of the wave barrier, relevant hydrodynamic parameters are computed using the wave-structure interaction simulation software ANSYS AQWA. These results serve as the basis for designing the WEC's drive system. Subsequently, a prototype of the device is fabricated and installed for experimental testing in a wave tank environment. Experimental results demonstrate that the device operates stably and achieves high performance.